Tinjauan Yuridis Pertanggungjawaban Pencemaran Minyak di Wilayah Teluk Balikpapan - Elisabeth Septin Puspoayu; Arief Rachman Hakim; Hanum Selsiana Bella (Fakultas Hukum Universitas Islam Indonesia, 2018)
Environmental pollution in Balikpapan Bay due to the leaking of Pertamina oil pipeline is a serious problem because it pollutes the marine ecosystem, resulting in disruption of environmental functions. However, the pollution caused by the burst pipeline due to the anchor of the MV Judger vessel cannot be directly imposed by the accountability mechanism as stipulated in Law on Environmental Protection and Management because there is no single factor in the incident. This paper aims to construct the form of accountability that must be done when an environmental pollution cannot be found as a single factorof error and involves the subject of international law outside the jurisdiction of the country where the pollution occurs. The type of research used is normative juridical. The result shows that joint accountability in the perspective of civil law is the best solution because the absence of a single factor and the existence of force majeure require that the parties involved in the shipping also be responsible for the pollution.